The Step into Existence: Reasoning toward God in Mendelssohn’s Morning Hours - Sánchez de León Serrano, José María (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article offers a detailed analysis of Moses Mendelssohn’s novel proof of God’s existence as developed in chapter 16 of his philosophical testament, Morning Hours. The paper reconstructs the logical structure of the argument, situates it within Mendelssohn’s broader philosophical outlook, and explores its far-reaching implications. It also investigates the possible historical sources and conceptual affinities of the argument. While some scholars have read Mendelssohn’s argument as a version of Berkeleyan idealism, others highlight its cosmological or anti-idealist dimensions. The article concludes by assessing the philosophical significance and limits of Mendelssohn’s approach, arguing that it offers a compelling, if ultimately contestable, attempt to reconcile finite cognition with metaphysical realism through the postulation of an infinite intellect.